ApoLink: Terhubung Langsung dengan Apoteker untuk Mendapatkan Layanan Kesehatan Terbaik - Hapsari, Wiranti Kusuma; Elah, Nur; Sulaiman R, M. Nur; Aryadhi, Alvin; Gobel, Yasin Anil Hakim; Sura, Priscila Biro (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2024)
The development of the digital era and technological advances have had a significant impact on various aspects of human life, including in the health sector. Information systems have become an important tool in presenting information effectively and efficiently. In this case, advances in the internet and telemedicine have changed the way health services are provided to the public. This research aims to develop an application called Apolink that connects directly with pharmacists, thus providing optimal health services. The research method used is qualitative with an emphasis on literature studies, interviews, and direct observation at the pharmacy. The research process includes analysis of system requirements based on drug data, customer data, sales data, and health consultations. In the analysis conducted, it was revealed that telemedicine services, such as consultations with doctors remotely, ordering medicines, and up-to-date health information, have many advantages. Telemedicine services can save time for doctors and patients, increase the accessibility of health services, and overcome geographic barriers. In addition, telemedicine can also reduce costs, improve medication adherence, and provide better clinical support. Based on this needs analysis, the Apolink application is developed with features that can meet user needs.